2022
DOI: 10.1039/d2cp01753a
|View full text |Cite
|
Sign up to set email alerts
|

Three-photon-induced singlet excited-state absorption for tunable ultrafast optical-limiting in distyrylbenzene: a first-principles study

Abstract: The ground and first singlet excited state absorption in distyrylbenzene(DSB) are simulated based on the linear-response time dependent density functional theory(LR-TDDFT). It is found that distyrylbenzene shows strong reverse saturable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 63 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…Our previous investigations revealed that trans -stilbene (TSB) has great potential as an OL material based on three-photon absorption-induced excited state absorption (3PA–ESA). 31 However, it is shown in the present paper that the main transitions of the GSA and ESA bands in TSB are mostly local excitations. Therefore, considering the descriptions in the above paragraphs, we designed four TSB derivatives with a D–π–A structure.…”
Section: Introductionmentioning
confidence: 46%
See 2 more Smart Citations
“…Our previous investigations revealed that trans -stilbene (TSB) has great potential as an OL material based on three-photon absorption-induced excited state absorption (3PA–ESA). 31 However, it is shown in the present paper that the main transitions of the GSA and ESA bands in TSB are mostly local excitations. Therefore, considering the descriptions in the above paragraphs, we designed four TSB derivatives with a D–π–A structure.…”
Section: Introductionmentioning
confidence: 46%
“…41 The validation of the present applied exchange–correlation functional has been illustrated in our previous work. 31,37,38 It was shown that the computational results obtained using the functionals with a roughly 50% HF component, for instance BHandHLYP, can be in good agreement with the experimental measurements. 31,37 This is also true for the present investigated molecule TSB, as will be shown in the coming sections.…”
Section: Methods and Computational Detailsmentioning
confidence: 76%
See 1 more Smart Citation
“…The presently applied exchange-correlation functional and the basis set also have been validated in the previous papers. 26,31,32 These calculations are performed for the molecules with ground state geometry due to the time needed for the geometry relaxation normally being longer than the ESA process. An elaborate discussion on the effect of geometry relaxation on ESA is given in ref.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…[28][29][30] In addition, the accuracy of this method has also been well tested. [31][32][33] This article is organized as follows. In the next section, we describe the methods and computational details to simulate the aggregation of ZnPc and the ESA.…”
Section: Introductionmentioning
confidence: 99%